2021
DOI: 10.48550/arxiv.2107.06897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Asymptotic Safety: Swampland or Wonderland?

Ivano Basile,
Alessia Platania

Abstract: We investigate the consequences of combining swampland conjectures with the requirement of asymptotic safety. To this end, we explore the infrared regime of asymptotically safe gravity in the quadratic one-loop approximation, and we identify the hypersurface spanned by the endpoints of asymptotically safe renormalization group trajectories. These comprise the allowed values of higher-derivative couplings as well as standard logarithmic form factors. We determine the intersection of this hypersurface with the r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…For the regions I, II where the approximation is valid, however, because u(1 + u) > 0 the contribution of this term is negative and deepens the AdS vacuum. 10 The mixing term of perturbative and non-perturbative corrections is a complicated function and can be elaborated in a similar manner. (63)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the regions I, II where the approximation is valid, however, because u(1 + u) > 0 the contribution of this term is negative and deepens the AdS vacuum. 10 The mixing term of perturbative and non-perturbative corrections is a complicated function and can be elaborated in a similar manner. (63)…”
Section: Discussionmentioning
confidence: 99%
“…For the recent debate on Swampland conjectures see for example [1][2][3] and related reviews [4][5][6]. Also, an incomplete list of 10d supergravity dS solutions and other related issues is [7][8][9][10][11][12] 4 For recent developments on related work see [15][16][17][18][19][20][21] the cosmological inflation have been studied. It was found that hybrid inflation is successfully implemented with the internal volume modulus acting as the inflaton [28], and the rôle of the waterfall field is played by open string excitations associated with the D7 brane stacks [29].…”
Section: Introductionmentioning
confidence: 99%